Association of iron indices and type 2 diabetes: a meta-analysis of observational studies - Orban, Ester; Schwab, Sigrid; Thorand, Barbara; Huth, Cornelia (Diabetes/metabolism research and reviews, 2014)
Summary The literature on the role of body iron status in the development of type 2 diabetes (T2D) in humans is inconsistent. We aimed to assess the association between iron indices and T2D by a meta‐analysis of previously published studies. A systematic literature search was conducted in PubMed and EMBASE. Observational studies on the association of ferritin (when controlled for age and sex), transferrin saturation, soluble transferrin receptor and transferrin with T2D were included. Pooled association estimates were calculated using a random effects model. Forty‐six eligible studies were identified. The pooled multivariable adjusted relative risks of T2D in the highest versus lowest quartile of ferritin levels were significantly elevated in both cross‐sectional as well as prospective studies and after restriction to inflammation‐adjusted studies [overall: 1.67 (95%CI 1.41‐1.99)]. The mean difference indicated 43.54 ng/mL (95%CI 28.14‐58.94) higher ferritin levels in type 2 diabetic individuals. The relative risk for a transferrin saturation ≥50% was 1.59 (95%CI 1.28‐1.97), the mean difference was −1.92% [95%CI −2.99‐(−0.85)]. Study‐specific results of soluble transferrin receptor and transferrin levels were extremely heterogeneous. Ferritin and clinically elevated transferrin saturation were strongly associated with an increased risk of T2D, overall and in prospective studies. Ferritin was also significantly associated after multivariable adjustment including inflammation. Thus, the current evidence hints at a causal effect; however, publication bias and unmeasured confounding cannot be excluded. Copyright © 2013 John Wiley & Sons, Ltd.